2014
DOI: 10.1111/1346-8138.12717
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant soybean tar Glyteer rescues T‐helper‐mediated downregulation of filaggrin expression via aryl hydrocarbon receptor

Abstract: Soybean tar Glyteer (Gly) has been widely used for the treatment of various inflammatory skin diseases in Japan since 1924 as an alternative to coal tar remedy. Recently, coal tar has been shown to induce barrier repair in atopic dermatitis via aryl hydrocarbon receptor (AhR). In this study, we demonstrated that Gly activated AhR by inducing its cytoplasmic to nuclear translocation in keratinocytes. The AhR ligation by Gly was biologically active, with significant and dose-dependent upregulation of CYP1A1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 34 publications
4
124
0
3
Order By: Relevance
“…Various phytochemicals and herbal extracts exert their antioxidant properties by activating the NRF2 system in an AHR-dependent or AHR-independent manner in human epidermal keratinocytes [18,19,20,21,22]. Certain antioxidant phytochemicals also upregulate the expression of filaggrin (FLG), which plays a pivotal role in maintaining epidermal barrier function [19,20,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Various phytochemicals and herbal extracts exert their antioxidant properties by activating the NRF2 system in an AHR-dependent or AHR-independent manner in human epidermal keratinocytes [18,19,20,21,22]. Certain antioxidant phytochemicals also upregulate the expression of filaggrin (FLG), which plays a pivotal role in maintaining epidermal barrier function [19,20,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…7,21 Our previous study has shown that steady-state OVOL1 expression is primarily present in the cytoplasm of NHEKs. 18 Ketoconazole, a potent AHR ligand, induces nuclear translocation of OVOL1 in NHEKs.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that FICZ and Glyteer upregulate FLG via the AHR − OVOL1 axis in NHEKs. Because the monolayer-cultured NHEKs system was difficult to use for evaluation of protein expression of FLG, including profilaggrin expression, 7 we utilized three-dimensionally (3D) cultured NHEKs. In the western blot analysis, FICZ and Glyteer yielded increased OVOL1 and FLG protein expression, which was normalized by CH-223191, a specific antagonist of AHR (Figure 3l).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations